Character Education Curriculum in the Government of Indonesia Strengthening Character Education Program - Ahmad Buchori Muslim (STIT Islamic Village Tangerang, 2020)
Character education is ethics education, character education, moral education, and value education which aims to shape each individual into a human with character, namely by planting positive character values so that they can be internalized in oneself and manifest in real action. Character education plays an important role in aspects of human life because being a human being with character will be able to live in a wider community dimension with a firm life principle. The Indonesian government has designed a program aimed at shaping cultured, quality, and character Indonesian people. In Presidential Regulation Number 87 of 2017 concerning strengthening character education, the government requires every educational institution in Indonesia both formal, informal, and non-formal to carry out the “Penguatan Pendidikan Karakter” (PPK) movement. The values that need to be instilled in character education include aspects of religion, humanity, and citizenship. In implementing character education, the principal must also involve all elements of the family, community, and school, and this education must be carried out continuously because character education is an education that will never end.